Dehydration of Date Palm (Phoenix dactylifera) Halves Using Different Drying Methods: DEHYDRATION OF DATE PALM HALVES - Desai, N N; Modi , V M; V V Modi (Annals of Arid Zone, 2024)
The date fruits are a food of high energy value. It is very popular both nationally and internationally. Date fruits are perishable fruit crops grown in the coastal region of Kutchh of Gujarat state A study was carried out to determine the drying characteristics of date halves using a hot air dryer, solar dryer, and open sun drying methods. The date halves were dried under a hot air flow dryer at temperature levels of 50, 60, and 70°C under pre-treatment of blanching. The rate of moisture of the blanched sample should only 7.5% reduction at 54 h drying period. In the case of date halves drying, the constant weight of the sample was achieved at 56 h of drying period in a solar cabinet dryer as compared to 320 h for open sun drying. The moisture content was reduced from 69.5 to 8.7% (w.b.) under a solar cabinet dryer for drying of 56 h, while the moisture content was reduced from 69.5 to 12.3% (w.b.) under open sun drying for a drying period of 320 h. The higher net return was obtained solar cabinet drying method as compared to the hot air flow dryer and open sun drying method. The cost of construction of a solar cabinet dryer is less than compared of a hot air flow dryer. The colour and flavour taste is superior in the case of solar cabinet dryer as compared to other dryers. Date halves dried at 70°C developed a dark brown colour, which might be due to higher drying temperatures. It resulted in higher selling prices to the growers. A higher net return (Rs. 89.83 kg-1) was obtained in the case of the solar cabinet dryer. Solar cabinet dryer and hot air flow dryer protects the produce from insect, bird damage, animals, excreta from rodents and birds, unseasonal rain, and wind storm. The solar cabinet dryer and hot air flow dryer could also be used to dry other farm produce like tomato chips, cowpeas, fennel, potato slices, coriander leaves, chilly, etc. It is used to adopt solar cabinet dryers for drying date halves.